SUSTAINABLE BUSINESS IMPROVEMENT AND ENVIRONMENTAL MANAGEMENT AND MONITORING OF SWADAYA PALM FARMERS TOWARDS SOCIAL BENEFITS - Siti Jaeni; Nurliza Nurliza; Dewi Kurniati (Jurnal Sains Pertanian Equator, 2019)
Social benefits are a reference in measuring the state of social relations as a result of independent oil palm plantations measured through sustainable aspects of business improvement and environmental management and monitoring raises the pros and cons of independent smallholders. These problems trigger the need for education of independent smallholders to have the knowledge and responsibility for the continuity of social benefits. The purpose of the study was to analyze the effect of sustainable business improvement as well as the management and monitoring of independent smallholder oil palm farmers' environment on social benefits. The respondents were selected purposively. Data analysis using Structural Equation Modeling (SEM) with Lisrel software research results showed that environmental management and monitoring had a positive effect on social benefits, with the most affected indicators being fire prevention and prevention, followed by report notes, implementation reports, environmental permits, documentation of rare animals & plants , the existence of rare animals & plants. Keywords : Social Benefits, Management and Environmental Monitoring, Sustainable Business Improvement, Structural Equation Modeling (SEM)